Mechanism of Implementing Technology in the Community of Eastern Indonesia (Case Study in Belu Regency– Nusa Tenggara Timur Province) - Rachmini Saparita; Savitri Dyah (STI Policy and Management Journal, 2020)
The strategy of implementing innovation and technology in the Belu Regency community is very important to be stated as best practice for other regions in Eastern Indonesia. This paper discusses a number of strategies that can be implemented as best practices for increasing community capability in using technology for managing and processing local resources by: technical training and continues coaching; providing equipment to target house-hold scale enterprises; and encourage Regional Governments to actively assist communities continually. Some strategies that fail in implementing technology in the regions are important lessons for us, that technology implementation requires adequate initial information, starting from location conditions, socio-economic of community, supporting infrastructure, human resource readiness, involvement and full support from the Regional Government. From long experience in Belu Regency, it can be a lesson for the technology implementation in Eastern Indonesia or in other regions that have similarities in community characteristics and natural conditions.